Avanti Communications Group plc secures satellite contract in Northumberland (Internet Business News, 2009)
Broadband satellite operator Avanti Communications Group plc (AIM: AVN) said on Monday that the company is the preferred bidder for the rollout of broadband services via satellite to Byrness and surrounding areas in Northumberland, subject to completion of standard contract documentation.